The Sigma1 Protein as a Target for the Non-genomic Effects of Neuro(active)steroids: Molecular, Physiological, and Behavioral Aspects - François P. Monnet; Tangui Maurice (Elsevier, 2006)
Abstract.: Steroids synthesized in the periphery or de novo in the brain, so called 'neurosteroids', exert both genomic and nongenomic actions on neurotransmission systems. Through rapid modulatory effects on neurotransmitter receptors, they influence inhibitory and excitatory neurotransmission. In particular, progesterone derivatives like α-hydroxy-5α-pregnan-20-one (allopregnanolone) are positive allosteric modulators of the γ-aminobutyric acid type A (GABAA) receptor and therefore act as inhibitory steroids, while pregnenolone sulphate (PREGS) and dehydroepiandrosterone sulphate (DHEAS) are negative modulators of the GABAA receptor and positive modulators of the N-methyl-D-aspartate (NMDA) receptor, therefore acting as excitatory neurosteroids. Some steroids also interact with atypical proteins, the sigma (σ) receptors. Recent studies particularly demonstrated that the σ1 receptor contributes effectively to their pharmacological actions. The present article will review the data demonstrating that the σ1 receptor binds neurosteroids in physiological conditions. The physiological relevance of this interaction will be analyzed and the impact on physiopathological outcomes in memory and drug addiction will be illustrated. We will particularly highlight, first, the importance of the σ1-receptor activation by PREGS and DHEAS which may contribute to their modulatory effect on calcium homeostasis and, second, the importance of the steroid tonus in the pharmacological development of selective σ1 drugs. Keywords:: neuro(active)steroid, sigma1 receptor, neurotransmission, neuronal plasticity, learning and memory